A fluorescent molecularly imprinted polymer sensor synthesized by atom transfer radical precipitation polymerization for determination of ultra trace fenvalerate in the environment. Issue 84 (26th August 2016) - Han, Wenjuan; Gao, Lin; Li, Xiuying; Wang, Liang; Yan, Yongsheng; Che, Guangbo; Hu, Bo; Lin, Xue; Song, Minshan
Abstract : In this study, novel fluorescence molecularly imprinted polymers (FMIPs) were prepared via atom transfer radical precipitation polymerization (ATRPP) for the optical detection of trace fenvalerate (FE). Abstract : In this study, novel fluorescence molecularly imprinted polymers (FMIPs) were prepared via atom transfer radical precipitation polymerization (ATRPP) for the optical detection of trace fenvalerate (FE). The FMIPs were characterized by FT-IR, SEM, LCSM, which demonstrated that the composite material exhibited a regular morphology and excellent monodispersity. The FMIPs showed high fluorescence intensity and highly selective recognition. Utilizing fluorescence quenching as a detecting tool, FMIPs were successfully used as a sensor to selectively and sensitively detect FE with a good linear relationship and a correlation coefficient of 0.9946 by the Stern–Volmer equation was obtained. Moreover, the experimental result also indicated good reproducibility via regeneration experiments and FMIPs as a type of fluorescent recognition sensor for FE was satisfactorily applied for environmental protection. Overall, this study demonstrated a good potential of FMIPs for the detection of FE in the environment.